The role of metrics in the governance of the water-energy-food nexus within the European Commission. (May 2022) - Voelker, Thomas; Blackstock, Kirsty; Kovacic, Zora; Sindt, Jan; Strand, Roger; Waylen, Kerry
Abstract: Recent years have witnessed a growing interest in the water-energy-food (WEF) nexus in both academia and policy. This concept draws attention to the link between different environmental and societal domains, and potentially entails substantive shifts in governance processes. As a consequence, policy-makers and scientists have started to develop metrics to make these interactions and 'trade-offs' visible. However, it is unknown if current framings of the nexus and relevant quantified metrics either reinforce or challenge existing governance structures. This paper explores relationships between framings of the nexus, metrics and models of governance based on discussions with staff within the European Commission. Although narratives around the need for new metrics are situated in a conventional script about the use of evidence to change policy, our data indicate processes of co-production, by which the use (or non-use) of any new metrics is dependent on existing institutional practices; and will reflect dominant political orderings. In doing so we provide a critical analysis of the role of metrics in environmental governance, and direct attention to the discursive, institutional and political arrangements in which they are embedded and with which they are co-constitutive. Focusing on the cultural and institutional settings in which they are established and used, our study suggests that the question of metrics in the water-energy-food nexus needs to be explored as a problem of establishing a legitimate policy objective in the European Commission and EU policy-making more broadly. Highlights: The water-energy-food nexus requires new approaches to policy-making. Quantitative metrics are needed to direct attention to system linkages. The term nexus is contested and marginal. Different framings are tied to ideas about the role of metrics for governance. Quantified metrics are not detached 'representations' of a world out there, but enrolled in 'messy' governance struggles and thus actors within a political and normative setting. Developing a nexus perspective and using nexus metrics are not challenges of information deficit, but speak to wider issues of institutional structures and cultures.